A Conformational Change in C-Reactive Protein Enhances Leukocyte Recruitment and Reactive Oxygen Species Generation in Ischemia/Reperfusion Injury - Thiele, Jan R.; Zeller, Johannes; Kiefer, Jurij; Braig, David; Kreuzaler, Sheena; Lenz, Yvonne; Potempa, Lawrence A.; Grahammer, Florian; Huber, Tobias B.; Huber-Lang, M.; Bannasch, Holger; Stark, G. Björn; et al. (Frontiers in Immunology, 2018)
Introduction: C-reactive protein circulates as a pentameric protein (pCRP). pCRP is a well-established diagnostic marker as plasma levels rise in response to tissue injury and inflammation. We recently described pro-inflammatory properties of CRP, which are mediated by conformational changes from pCRP to bioactive isoforms expressing pro-inflammatory neo-epitopes (pCRP* and mCRP). Here, we investigate the role of CRP isoforms in renal ischemia/reperfusion injury (IRI). Methods: Rat kidneys in animals with and without intraperitoneally injected pCRP were subjected to IRI by the time of pCRP exposure and were subsequently analyzed for monocyte infiltration, caspase-3 expression and tubular damage. Blood urea nitrogen (BUN) was analyzed pre-ischemia and post-reperfusion. CRP effects on leukocyte recruitment were investigated via intravital imaging of rat striated muscle IRI. Localized conformational CRP changes were analyzed by immunohistochemistry using conformation specific antibodies. 1,6-bis(phosphocholine)-hexane (1,6-bisPC), which stabilizes CRP in its native pentameric form was used to validate CRP effects. Leukocyte activation was assessed by quantification of reactive oxygen species (ROS) induction by CRP isoforms ex vivo and in vitro through electron spin resonance (ESR) spectroscopy. Signaling pathways were analyzed by disrupting lipid rafts with nystatin and subsequent ROS detection. In order to confirm the translational relevance of our findings, biopsies of microsurgical human free tissue transfers before and after IRI were examined by immunofluorescence for CRP deposition and co-localization of CD68+ leukocytes. Results: The application of pCRP aggravates tissue damage in renal IRI. 1,6-bisPC reverses these effects via inhibition of the conformational change that leads to exposure of pro-inflammatory epitopes in CRP (pCRP* and mCRP). Structurally altered CRP induces leukocyte-endothelial interaction and induces ROS formation in leukocytes, the latter can be abrogated by blocking lipid raft dependent signaling pathways with Nystatin. Stabilizing pCRP in its native pentameric state abrogates these pro-inflammatory effects. Importantly, these findings are confirmed in human IRI challenged muscle tissue. Conclusion: These results suggest that CRP is a potent modulator of IRI. Stabilizing the native pCRP conformation represents a promising anti-inflammatory therapeutic strategy by attenuation of leukocyte recruitment and ROS formation, the primary pathomechanisms of IRI.